Put Yourself out There! A Strategy for Effective Self-Promotion in Academic Medicine - Adam D. Wolfe; Lydia K. Davidson; Caroline R. Paul (Association of American Medical Colleges, 2024)
Introduction Trainees and faculty in academic medicine often struggle with self-promotion. Barriers may be more formidable for women and other groups underrepresented in medicine. Experience-based stories illustrating personal strengths are preferable when engaging in self-promotion activities. Methods We developed a 90- to 120-minute workshop utilizing approaches such as iterative journaling and peer discussion to teach the development of problem-action-result (PAR) stories for self-promotion efforts in interviews and written applications to new positions. Participants provided Likert-scale (1 = strongly disagree, 5 = strongly agree) and free-response evaluations, which we analyzed for workshop strengths and areas for improvement. Results We presented the workshop in person to 28 pediatric residents and subsequently to 22 residents, fellows, and faculty at an in-person national meeting. Sixty-one percent of the resident group and 100% of the national workshop group completed the evaluation. Both groups reported high satisfaction with the workshop's format (M = 4.7) and content (M = 4.7) and indicated intention to use the skills learned (M = 4.7). Strengths included the PAR format, interactivity, journaling, opportunity for reflection, and tips for interviewing and writing. Areas to improve included offering the workshop earlier in the academic year and providing more written examples of PAR stories. Discussion This workshop used strategies of personal reflection, journaling, and peer feedback to help participants understand behavior-based recruiting practices and the PAR framework as a strategy for successful self-promotion. Learners can use these strategies to develop greater confidence and efficacy and to address barriers to effective self-promotion they encounter.